Hitler's Birthday Parade (Germany, 1939)
This complete Nazi propaganda newsreel shows Berlin - adorned with flags and floral displays by its citizens and monolithic statuary designed by Albert Speer - preparing for the holiday: the 50th birthday of Adolf Hitler. Part of the festival is the greatest military demonstration in the history of the Third Reich.
Keywords: Newsreels